2020
DOI: 10.1007/s10637-020-00925-2
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib, a novel VEGFR-2 tyrosine kinase inhibitor, for relapsed and refractory nasopharyngeal carcinoma: data from an open-label, single-arm, exploratory study

Abstract: Summary Purpose Apatinib, a new tyrosine kinase inhibitor targeting vascular endothelial growth factor receptor-2, has shown promising efficacy against several solid cancers, but evidence of its efficacy against relapsed and refractory nasopharyngeal carcinoma is limited. We investigated the efficacy and safety of apatinib for relapsed and refractory nasopharyngeal carcinoma in an open-label, single-arm, phase II clinical trial. Fifty-one patients with relapsed and refractory nasopharyngeal carcinoma in the Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 31 publications
1
20
1
Order By: Relevance
“…As second-line and above treatment, the mOS of single-agent apatinib in nasopharyngeal carcinoma was 6.5 months, and no mPFS was obtained. The mOS of our study was much lower than the other study 19 . We compared patient baselines and treatment modalities with this study.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…As second-line and above treatment, the mOS of single-agent apatinib in nasopharyngeal carcinoma was 6.5 months, and no mPFS was obtained. The mOS of our study was much lower than the other study 19 . We compared patient baselines and treatment modalities with this study.…”
Section: Discussioncontrasting
confidence: 87%
“…Apatinib combined with carrelizumab in the treatment of advanced osteosarcoma, triple-negative breast cancer, advanced cervical cancer, advanced esophageal squamous cell carcinoma, and extensive-stage small cell lung cancer have obtained very good curative effects with acceptable safety 14 18 . In a previously published clinical study on the efficacy and safety of single-agent apatinib for relapsed/metastatic nasopharyngeal carcinoma that had failed previous chemotherapy, the median OS and PFS were 16 (95% confidence interval [CI], 9.3–22.7) and 9 months (95% CI 5.2–12.8), respectively 19 . This is the valuable clinical data regarding apatinib in the treatment of recurrent/metastatic head and neck malignancies so far, but comprehensive clinical data are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the apatinib can inhibit the growth of nasopharyngeal carcinoma xenografts [ 22 ]. There is also a retrospective study, which shows that apatinib has good efficacy and safety in patients with recurrent and refractory nasopharyngeal carcinoma [ 23 ]. However, there is a lack of clinical control studies on the apatinib in the treatment of nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated an ORR of 31.4% (16/51), with a median PFS of 9 months and OS of 16 months. 8 A phase II study also investigated the treatment efficacy of pazopanib in 33 patients with NPC. The ORR was 6.1% and the DCR was 54.5% at 3 months.…”
Section: Assessment Analysis and Discussionmentioning
confidence: 99%